2012
DOI: 10.1186/1477-7525-10-150
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Danish version of the disease specific instrument EORTC QLQ-CR38 to assess Health-related quality of life in patients with colorectal cancer

Abstract: BackgroundThe European Organisation for Research and Treatment of Cancer (EORTC) quality of life colorectal questionnaire module (QLQ-CR38) was developed in 1999, and an update, the QLQ CR29 was published recently. To date the Danish version of the questionnaire has not been validated. The aim of this study was to examine the psychometric properties of the Danish version of EORTC QLQ-CR38.MethodsEORTC QLQ-CR38 was administered to 190 patients with colorectal cancer in two Danish hospitals, one month after thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
(37 reference statements)
0
14
0
1
Order By: Relevance
“…The patients in our sample scored markedly lower than those in the Spanish study, likely reflecting in part cultural values about body image and sexuality. Dysuria had similar high floor effects in the Spanish [ 5 ] and Danish [ 6 ] studies. We recommend additional assessment of the items urinary incontinence and dysuria, which showed poor reliability and item performance.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The patients in our sample scored markedly lower than those in the Spanish study, likely reflecting in part cultural values about body image and sexuality. Dysuria had similar high floor effects in the Spanish [ 5 ] and Danish [ 6 ] studies. We recommend additional assessment of the items urinary incontinence and dysuria, which showed poor reliability and item performance.…”
Section: Discussionmentioning
confidence: 79%
“…Later validation studies were reported for the Polish [ 4 ] and Spanish [ 5 ] versions. Validation of the Danish QLQ-CR38 [ 6 ] suggested the QLQ-CR29 to be more valid than the QLQ-CR38. In the Spanish QLQ-CR29, the blood and mucus scale was not confirmed; in the Polish only the body image scale was reliable, and the urinary incontinence scale approached acceptable reliability.…”
Section: Introductionmentioning
confidence: 99%
“…A high rate of non-response to questions about sexual functioning is a common research finding (e.g. [62][63][64]), no doubt due to the highly personal nature of the topic. The large number of missing responses for item 15, which enquires about reluctance to "start new relationships", may indicate that many participants interpreted this question as enquiring about romantic or sexual relationships, rather than platonic friendships.…”
Section: Discussionmentioning
confidence: 98%
“…The initial 6 scales and 11 items construct of the QLQ-CR29 was reformatted into the final structure of 4 scales and 17 items. Thaysen et al have summarized that EORTC QLQ-CR29 contains 17 unchanged questionnaire items from the QLQ-CR38, 5 reworded items, and 7 new items [ 24 ].…”
Section: Discussionmentioning
confidence: 99%